Development of domino media to improve problem solving and mathematical communication for Islamic boarding school students - Nur Hidayah; Moh. Mahfud Effendi; Alfiani Athma Putri Rosyadi (Universitas Muhammadiyah Malang, 2024)
Mathematical problem solving and communication skills are important factors in learning mathematics. Therefore, it is necessary to develop learning media, especially in Islamic boarding school curricula where the learning load is greater than the regular curriculum. On this basis, the aim of this research is to develop domino card media to improve problem solving and mathematical communication skills of Islamic boarding school students. Development was carried out at Al-Izzah IIBS Batu Middle School, Malang, using the ADDIE model. Data obtained from documents, observations, questionnaires and tests were analyzed using qualitative and quantitative approaches. Based on the results of the validation analysis, the domino card media was declared valid from the aspects of design, material, curriculum, consistency, language, practicality, problem solving development and mathematical communication. Meanwhile, the effectiveness of using domino card media in learning is classified as effective, if seen from the results of the problem solving ability test with an N-Gain score of 76.79%, and the results of the mathematical communication ability test with an N-Gain score of 61.79%. Many factors cause this non-optimality, including a lack of mathematics lesson hours, a busy lesson schedule that is less suited to conditions, many demands on students, and the learning load in the curriculum.